THE ROLE AND CONTRIBUTION OF WOMEN FARMERS TO CASHEW FARMING INCOME ON MADURA ISLAND - Nanda Hari Pramudya; Dwi Ratna Hidayati; Nor Qomariyah (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
Women in farming activities have the same role as men, but their role is often ignored. Women are considered not to have a significant impact on farming activities. The aim of this research is to determine the role and contribution of women cashew farmers, determine cashew farming income, and determine the relationship between the involvement of women farmers and cashew farming income. The approach to understanding women's contributions in cashew farming uses the Harvard Method perspective (activity, marketing, access, control and benefits). This research used a mixed-method approach carried out on Madura Island, especially in Sampang and Sumenep Regencies. The qualitative approach used in-depth interviews with six key informants from the Agriculture and Agricultural Extension Services in the two districts. Furthermore, quantitative research involved a sample of 40 women cashew farmers from Sampang and Sumenep Regencies. The analysis stage uses distribution frequency, farming income analysis, and chi-square analysis. The results of this research show that in general women are involved in all categories (activities, marketing, access, control and benefits) with an average income of IDR 18,909,474. However, there is no relationship between the involvement of women farmers and cashew farming income. Therefore, further exploration of gender-sensitive research on women farmers is needed for the development of the cashew sector.